2006
DOI: 10.1152/ajprenal.00001.2004
|View full text |Cite
|
Sign up to set email alerts
|

Branching ducts similar to mesonephric ducts or ureteric buds in teratomas originating from mouse embryonic stem cells

Abstract: Ureteric bud epithelial cells and metanephric mesenchymal cells that comprise the metanephric kidney primordium are capable of producing nephrons and collecting ducts through reciprocal inductive interaction. Once these cells are induced from pluripotent embryonic stem (ES) cells, they have the potential to become powerful tools in the regeneration of kidney tissues. In this study, we investigated these renal primordial cells and structures in mouse ES cell outgrowths and their transplants. Gene expression ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 47 publications
1
40
0
1
Order By: Relevance
“…An impressive case for renal promodial-like ducts induced from mouse ES cells was reported (Yamamoto et al, 2005). They allowed the outgrowth of ES cell-derived embryoid bodies for a week in vitro, then the harvested cells were transplanted to adult nu/nu host retroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…An impressive case for renal promodial-like ducts induced from mouse ES cells was reported (Yamamoto et al, 2005). They allowed the outgrowth of ES cell-derived embryoid bodies for a week in vitro, then the harvested cells were transplanted to adult nu/nu host retroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to technical risks, in vivo injection of these pluripotent cells can give rise to teratomas, as demonstrated by Yamamoto et al [57], who reported the generation of teratomas containing metanephric-mesenchyme-related structures after injection of undifferentiated ES cells within the peritoneum of nude mice [57]. In contrast, Steenhard et al [58] reported a 50% integration of undifferentiated ES cells into the tubules of embryonic kidneys without evidence of teratoma formation.…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%
“…While impressive, the developing kidney may better provide the full signals required to direct onward renal tubular development than an adult kidney. Yamamoto et al (72) did not direct their murine ES cells in any way. Conventional EB culture also induced the expression of most of the markers that were seen by Kim and Dressler (75).…”
Section: Human Es Cellsmentioning
confidence: 99%